Meningkatkan Minat Dan Hasil Belajar Siswa Melalui Bimbingan Belajar Menggunakan Alat Peraga Rangkaian Listrik - Januaris Pane; Asnida Nainggolan; Juliper Nainggolan; Bajongga Silaban; Riossally Marselina Tumanggor (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Learning that occurs in schools certainly has many obstacles and difficulties for students. As a result of online learning that was previously done, many students did not understand the learning material. Learning that occurs and takes place for students in science lessons, especially physics, has been a difficult lesson because of the many formulas and theories that tend to be memorized so that students feel less interested. In physics lessons, experiments are needed to improve students' understanding, so tutoring is carried out after school to overcome students' difficulties using teaching aids with the experimental method. Community service activities with tutoring are carried out at SMP Negeri 1 Tapian Nauli. Props used in electrical circuit material. With props that have been made can help students gain understanding and maximum learning outcomes in the tutoring carried out. The development of this electric circuit aid helps students to practice skills and understanding on series circuits and parallel circuits. The results of this tutoring activity increased student interest and learning outcomes, seen the average value of students before using the electric circuit teaching aid was 34.69 and after using the electric circuit teaching aid 86.57. Based on the N-Gain analysis, it is known that student learning outcomes are categorized as high and the results of the T test (Paired Sample Test) show a significant difference. The electric circuit teaching aids developed are very feasible, practical and effective to use in learning for students.